Mineral Composition, Physico-chemical Properties and Fatty Acids Profile of Prunus armeniaca Apricot Seed Oil - Shariatifar, Nabi; Pourfard, Issa Mohammad; Khaniki, Gholamreza Jahed; Nabizadeh, Ramin; Akbarzadeh, Arash; Mozaffari Nejad, Amir Sasan (Asian Journal of Chemistry, 2017)
Apricot (Prunus armeniaca L.) kernel oil is obtained from the kernels (seeds) of apricots. This research aimed to investigate the physico-chemical properties of wild apricot kernel oil. The apricot oils tested in this study showed a high content of unsaturated and low saturated fatty acids. Significant differences existed between the physico-chemical indices of different wild apricot kernel oil. The meaning of peroxide value (meq/kg), acid value, iodine value and saponification number of wild apricot kernel oil were 0.67375, 0.48625, 100.27 and 1089.06, respectively. The mean rate of oil contents in wild apricot kernels varied from 38 to 55.3 %. Oleic acid (60.01-70.56 %) is the key fatty acid found in wild apricot kernel oil, followed by linoleic acid (19.74-23.52 %) and palmitic acid (2.35-5.97 %). The results showed that the physical and chemical characteristics of apricot kernel oil samples were favourable for edible and pastry industry.